1986
DOI: 10.1016/0014-5793(86)81003-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological properties of two dimeric forms of human α‐atrial natriuretic peptide

Abstract: Two dimeric forms of human a-atria1 natriuretic peptide (a-ANP) were synthesized by solution methods and compared with monomeric a-ANP in terms of some biological and immunochemical properties. The parallel form @'-ANP) and the antiparallel form (B-ANP) were equipotent in smooth muscle relaxant activity in isolated rat aorta and their ED,, values were estimated to be 1.7 x lo-* M and 1.6 x 10e8,M, respectively. Diuretic and natriuretic responses induced by fi-ANP and ,Y'-ANP in anesthetized rats were equally l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…It has recently been shown that synthetic phANP, an antiparallel dimer of cu-hANP, has biological properties similar to natural ,&hANP [4,5]. The present study first demonstrates that synthetic &hANP binds to cultured rat VSMCs in the same manner as a-hANP in terms of time-and temperature-dependency.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…It has recently been shown that synthetic phANP, an antiparallel dimer of cu-hANP, has biological properties similar to natural ,&hANP [4,5]. The present study first demonstrates that synthetic &hANP binds to cultured rat VSMCs in the same manner as a-hANP in terms of time-and temperature-dependency.…”
Section: Discussionsupporting
confidence: 62%
“…Division, National Cardiovascular Center Research Institute, S&a, Osaka 565, Japan been synthesized and its biological activity has been determined [4,5]. Interestingly, natural [2] as well as synthetic fi-hANP [4,5] exhibits a slower onset and longer duration of action than a-hANP, the mechanism of which remains obscure.…”
Section: Hypertensionendocrinementioning
confidence: 99%
See 1 more Smart Citation
“…Although the characteristic pattern of action of ,&ANP in vasorelaxation and natriuresis [2,3] may be explained, at least in part, by the slow conversion of ,&ANP into a-ANP in human plasma or at target tissues [5-7,161, it has been a matter of controversy as to whether fl-ANP itself is biologically active. The present investigation has also shown that ,&ANP inhibits the a-ANP-induced production of intracellular cGMP in cultured VSMC with an apparent ICSO value of 2.13 x lo-' M, which is about one-third that of analog III and this ratio is comparable to that one between the 1% values of &ANP and analog III for receptor binding.…”
Section: Discussionmentioning
confidence: 99%
“…Human cu-ANP and &ANP [3] were synthesized by solution methods in these laboratories. '251-labeled human (u-ANP (1800 Ci/mmol) was purchased from Amersham and aminopeptidase M from Pierce.…”
Section: Methodsmentioning
confidence: 99%